Perceived information provision and information needs in adolescent and young adult cancer survivors. (27th July 2018) - Christen, Salome; Weishaupt, Esther; Vetsch, Janine; Rueegg, Corina S.; Mader, Luzius; Dehler, Silvia; Michel, Gisela
Abstract: Knowledge on former diagnosis, treatment and survivorship is important for adolescent and young adult cancer survivors (AYACS) to make informed healthcare decisions. We aimed to (a) describe the information AYACS reported to have received, (b) identify current information needs and survivors' preferred format of communication, and (c) examine associations between information needs and cancer‐related/socio‐demographic characteristics, psychological distress and health‐related quality of life (HRQoL). We identified AYACS (16–25 years at diagnosis; ≥5 years since diagnosis) through the Cancer Registry Zurich and Zug. Survivors received a questionnaire on information received and current information needs, socio‐demographic information, psychological distress (Brief Symptom Inventory‐18) and HRQoL (SF‐12). Clinical characteristics were available from the cancer registry. We used descriptive statistics and univariable regression models. Of 160 responders, most reported to have received information on disease (96.3%), treatment (96.3%) and follow‐up (89.4%), fewer on late effects (63.1%). Survivors reported information needs on late effects (78.7%), follow‐up (71.3%), disease (58.1%) and treatment (55.6%). Information needs were associated with experiencing psychological distress and lower mental HRQoL. Most Swiss AYACS have information needs, especially on follow‐up and late effects. Therefore, AYACS should be personally, continuously and proactively informed about their disease, treatment, follow‐up care and late effects.